WAHDAH ISLAMIYAH DALAM MEMBENTUK KARAKTER MASYARAKAT DI KOTA KENDARI - Purwana, Nanang; Suyuti, Nasruddin; Momo, Abdul Halim (Jurnal Penelitian Budaya, 2021)
The purpose of this study is to examine and understand the forms, functions, values, moral change of the people of Kendari City after getting a character education provided by Wahdah Islamiyah. In this study, the data were obtained through structured observation and interviews of 12 administrator of Wahdah Islamiyah Kendari and 17 Kendari City resident who participated in character building in Wahdah Islamiyah of Kendari City, and conducted observations on matters relating to character building carried out by Wahdah Islamiyah towards the people of Kendari City. Furthermore, all research objects were analyzed qualitatively descriptive. The results showed that the character building carried out by Wahdah Islamiyah towards the people of Kendari City is a goal that was not contrary to the goal of character building launched by the Kendari City government towards its people. In order to increase the faith and piety of the people of Kendari City, the government has launched a program to liberate the illiteracy of the Qur'an and improve the morals of the people of Kendari City. In line with what was done by Wahdah Islamiyah who did the character building of the city of kendari by using several coaching approaches namely the mental and spiritual coaching approach, leadership, training, academic, competition, and amaliya. All of these approaches function to make the people of Kendari City have good character values and have strong in faith and devotion to Allah Subhanahu Wata’ala. The character values contained in the character building carried out by Wahdah Islamiyah towards the people of Kendari City are religious values, tolerance, discipline, hard work, honesty, respect for achievement, care for the environment, care for the social and responsibility. The values of the formation of these characters can be identified from the activities carried out by the people who participate in coaching in Wahdah Islamiyah as well as from their attitudes and behavior patterns after they get character development done by Wahdah Islamiyah in Kendari City.Keywords: Formation of character by Wahdah Islamiyah, form, function, and character values of the people of Kendari City.